Perception of patriotic entrepreneurship in Poland and Ukraine - Łukasz Sułkowski; Grzegorz Ignatowski; Bartłomiej Stopczyński; Joanna Sułkowska (Entrepreneurial Business and Economics Review (EBER), 2022)
Objective: The article aims to investigate how patriotic entrepreneurship is understood by Polish and Ukrainian entrepreneurs. Research Design & Methods: Qualitative research was carried out as part of the research conducted on the opportunities presented by the development of patriotic entrepreneurship. As part of the qualitative research, in-depth individual inter-views were conducted with ten entrepreneurs doing business in Poland and Ukraine. Findings: The results showed that the concept of patriotic entrepreneurship was positively evaluated by the entrepreneurs and should be expressed in greater entrepreneurial independence. In their answers, the entrepreneurs paid attention to the need to 'humanise' entrepreneurship. They also showed understanding and strong support for consumer ethnocentrism, which is one of the dimensions of patriotic entrepreneurship. Patriotic entrepreneurship is also determined by preferences as to where a business is conducted. Respondents also indicated that the best place to do business was their own country of origin, empowering their own business, which increases independence from international consortia. Implications & Recommendations: Patriotic entrepreneurship can be one of the important motivations for consumer, managerial, and employee actions. Contribution & Value Added: The study was exploratory in nature. Due to the very scarce literature in the field of patriotic entrepreneur-ship, it will serve as a basis for future research in the mentioned area. By systematising the knowledge in this area, it will be possible to better prepare future research projects in this area.
Keywords: M02; O02; 330; patriotism; nationalism; patriotic entrepreneurship; economic entrepreneurship; consumer ethnocentrism